2023
DOI: 10.1155/2023/6226200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Pulmonary Tuberculosis among Prison Inmates in Sub-Saharan Africa: A Systematic Review and Meta-Analysis

Habtamu Belew Mera,
Fasil Wagnew,
Yibeltal Akelew
et al.

Abstract: Introduction. Prisoners in Sub-Saharan Africa (SSA) are at a high risk of tuberculosis (TB) infection due to overcrowding and poor ventilation. Consequently, TB is a leading cause of morbidity and mortality in prison, and many inmates face a number of barriers to TB control and had limited information in the region. Thus, the aim of this systematic review and meta-analysis was to estimate the overall pooled prevalence of pulmonary TB and predictors among prison inmates in SSA. Methods. From 2006 to 2019, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
3
0
0
Order By: Relevance
“…The current study found a strong statistical relationship between the magnitude of TB and the duration of imprisonment (adjusted odds ratio = 1.29 [95% CI: −0.39-2.97]), with the risk of TB increasing with the duration of imprisonment for those prisoners whose duration of incarceration is short. This result was consistent with previous studies conducted in SSA, 46 South Africa, 48 and India. 66 This might be because prisoners are not in a closed system, due to the number of people entering, departing, and reentering and the poor environmental situation, possibly increasing the transmission probability.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The current study found a strong statistical relationship between the magnitude of TB and the duration of imprisonment (adjusted odds ratio = 1.29 [95% CI: −0.39-2.97]), with the risk of TB increasing with the duration of imprisonment for those prisoners whose duration of incarceration is short. This result was consistent with previous studies conducted in SSA, 46 South Africa, 48 and India. 66 This might be because prisoners are not in a closed system, due to the number of people entering, departing, and reentering and the poor environmental situation, possibly increasing the transmission probability.…”
Section: Discussionsupporting
confidence: 94%
“…The odds of developing TB were 2.75 times higher among prisoners who had a history of contact with TB patients as compared to their counterparts. It agrees with the findings conducted in SSA 46 and India, 66 which reported 2.43 and 3.64 times more infected, respectively. This might be because they are more likely to be exposed to TB bacteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation